Fitness of Young Athletes: A Comparison of Lifestyles of Smoking and Non-Smoking Athletes - Rizky Naufal; Gugun Gunawan; Indra Sholehudin (Journal of Physical and Outdoor Education, 2025)
This study aims to determine the comparison between smokers and non-smokers on the level of physicalfitnessin U-17 futsal athletes at the Arjuna FCfutsal club. The population of all futsal athletes at the Arjuna Fc club. Sampling was carried out using the quota sampling technique, namely 24 athletes consisting of 12 smoking athletes and 12 non-smoking athletes. There is a difference in the average VO2max value of smoking and non-smoking athletes, the average VO2max value of non-smoking athletes is higher than that of smoking athletes. So that way the physical fitness of non-smoking athletes is better than that of smoking athletes. The results of data analysis for theoverall percentage of physical fitness elements (VO2max) of 12 smoking athletes and 12 non-smoking athletes at the Arjuna Fc futsal club in the Superior category were (4%) or as many as 1 athlete, in the Excellent category (21%) or as many as 5 athletes, in the Good category (50%) or as many as 12 athletes, in the Fair category (25%) or as many as 6 athletes.